2013
DOI: 10.3109/09537104.2013.790013
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationship between serum uric acid and mean platelet volume in a Japanese general population

Abstract: Mean platelet volume (MPV) can reflect platelet activity. Furthermore, high MPV is associated with thrombogenic activation and increased risk of cardiovascular disease. MPV of subjects with hypertension, hyperglycemia, or hyperlipidemia is higher compared with that of normal subjects. In contrast, the relationship between MPV and uric acid (UA) is poorly understood. The present study aims to evaluate the relationship between MPV and serum UA levels in both genders. We retrospectively studied 2104 Japanese subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…Increased insulin resistance and other components of the metabolic syndrome were earlier shown to be associated with increased white and red blood cell count, hemoglobin, and hematocrit, and as a consequence, increased blood viscosity [14]. Our finding of no correlation between serum uric acid and platelet count and mean platelet volume was contrary to other reports [15] Although there is some evidence linking increased white and red blood cell count, hemoglobin, and hematocrit with hyperuricemia, role of confounding variables like chronic inflammation and obesityassociated obstructive sleep apnea cannot be ruled out.…”
Section: Discussioncontrasting
confidence: 86%
“…Increased insulin resistance and other components of the metabolic syndrome were earlier shown to be associated with increased white and red blood cell count, hemoglobin, and hematocrit, and as a consequence, increased blood viscosity [14]. Our finding of no correlation between serum uric acid and platelet count and mean platelet volume was contrary to other reports [15] Although there is some evidence linking increased white and red blood cell count, hemoglobin, and hematocrit with hyperuricemia, role of confounding variables like chronic inflammation and obesityassociated obstructive sleep apnea cannot be ruled out.…”
Section: Discussioncontrasting
confidence: 86%
“…Studies had reported a significant correlation between SUA and platelet count and mean platelet volume. 18 In addition, several theories implicated that elevated SUA was a causative factor for increasing platelet reactivity, but SUA levels did not influence platelet aggregation. 17,19 A previous study observed a significant relationship between SUA and mean platelet volume, and this association was stronger in women than men.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 A previous study observed a significant relationship between SUA and mean platelet volume, and this association was stronger in women than men. 18 Platelet abnormalities occurred with hyperuricemia. Altered platelet kinetics played a role in arterial thrombosis and possibly in the genesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there was a sex effect on the relationship of blood pressure and platelet indices. [18,4951] Those studies suggested that only partial indicators of platelet indices reflect the disease severity. From our findings, we can suggest that an elevated MPV and PDW might be an indication to recognize the part of platelet activation in the interpretation of the cause of hypertension.…”
Section: Discussionmentioning
confidence: 99%